Water Management District Considerations for Florida Citrus Groves - Brian Boman; Larry Parsons (EDIS)
This is document No. CH192 and Circular 1422, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: September 2002.